Use of autologous fat grafting for the correction of burn scar contracture in the hand: a case report. Issue 1 (1st January 2017) - Al-Hayder, Shems; Gramkow, Christina; Trojahn Kølle, Stig-Frederik
Abstract: Severe burn injuries to the hand represent a topic of great concern due to long-term complications such as hypertrofic burn scar and contracture, which may result in loss of function. We present a case of burn scar contracture in the hand of a child undergoing Z-plasty and lipofilling.